Dewan Perwakilan Daerah dan Kewenangannya dalam Sistem Ketatanegaraan Republik Indonesia - Hulman Panjaitan (to-ra, 2015)
Dewan Perwakilan Daerah Republik Indonesia (DPD RI) was born as a result of reform on Amendment 1945 Constitution, for the needs to answer matters relations central and regional. The constitution orders to keep NKRI, that is acted upon by the provision of regional autonomy. DPD, as a state institution,which born from reformation spirit to speed up the development so should also as parliament and the president also have the authority to discuss the bill, particularly those relating to regional autonomy, the center and regions, formation, segregation and amalgamation regions, the management of natural resources and other economic resources and related financial balance center and regions, like the one in article 22D constitution 1945 and supported by verdict MK Number 92 /PUU-X /2012 and verdict MK number 79/PUU-XII/2014.Kata Kunci : Dewan Perwakilan Daerah, Sistem Ketatanegaraan Republik Indonesia